Geodiversity of Italy - Annarita Casaburi; Ines Alberico; Fabio Matano (Journal of Maps)
In recent years, natural areas have been exposed to increasing anthropogenic pressure related to the growing need for natural resources. Comprehensive information on the geodiversity of a territory is essential for all stakeholders in order to define effective land management toolsusefull for preserving the natural heritage for future generations. We computed geodiversity map as the summary of lithological, morphological, paedological indicators and hydrological index using a workflow based on the grid analysis, performed in a Geographic Information System environment. The geodiversity map of Italy (main map) provides a synoptic view of the geographical distribution of the abiotic component of the landscape ranked into five classes varying from very high to very low geodiversity. This map is supplemented by histograms showing the percentages of geodiversity classes for each Italian region and a Regional Geodiversity Index map that assigns a geodiversity value to each Italian region.